Transcriptome analysis reveals the molecular mechanisms underlying growth superiority in a novel grouper hybrid (Epinephelus fuscogutatus♀ × E. lanceolatus♂). Issue 1 (December 2016) - Sun, Ying; Guo, Chuan-Yu; Wang, Deng-Dong; Li, Xiao; Xiao, Ling; Zhang, Xinhui; You, Xinxin; Shi, Qiong; Hu, Guo-Jun; Fang, Chao; Lin, Hao-Ran; Zhang, Yong
Abstract Background Groupers (Epinephelus spp.) have been widely cultivated in China and South-East Asian countries. As a novel hybrid offspring crossed betweenE. fuscogutatus ♀ andE. lanceolatus ♂, Hulong grouper exhibits significant growth superiority over its female parent, which made it a promising farmed species in grouper aquaculture industry in China. Hulong grouper present a good combination of beneficial traits from both parent species, but the molecular mechanisms of its heterosis still remain poorly understood. Results Based on RNA sequencing and gene expression profiling, we conducted comparative transcriptome analyses between Hulong grouper and its parentsE. fuscoguttatus & E. lanceolatus . Six hundred sixty-two and 5239 differentially expressed genes (DEGs) were identified in the brains and livers, respectively. GO enrichment analysis of these DEGs revealed that metabolic process and catalytic activity were the most enriched GO terms. Further analysis showed the expressions ofGnRH1 andGnRH3 in the brain, and GH/IGF axis related genes such asIGF-1, IGF-2b, IGFBP-1, IGFBP-2, IGFBP-4 andIGFBP-5a in the liver of the hybrid F1 were significantly up-regulated, which is in accordance with the growth superiority of hybrid grouper. Meanwhile, expressions of genes related to the protein and glycogen synthesis pathway, such asPI3KC, PI3KR, Raptor, EIF4E3, andPP1 were up-regulated, whilePYG expression was down-regulated. These changes might contribute to increased protein and glycogen synthesis in the hybrid grouper. Conclusions We identified a number of differentially expressed genes such asGnRH1 andGnRH3, and genes involved in GH/IGF axis and its downstream signaling pathways for protein and glycogen synthesis in Hulong Grouper. These findings provided molecular basis underlying growth superiority of hybrid grouper, and comprehensive insights into better understanding the molecular mechanisms and regulative pathways regulating heterosis in fish.